A STATE-WISE ANALYSIS ON GOVERNMENT SPONSORED HEALTH INSURANCE SCHEMES IN INDIA - Dr.V.Pugazhenthi (EPRA International Journal of Economic and Business Review(JEBR), 2022)
Government Sponsored Health Insurance Schemes (GSHISs) are those health insurance schemes which are subsidized fully or partly by the Union or State Government or both in India. This may be for the welfare of its poor people or for a section of people like employees, pensioners journalists, etc. In this paper the GSHISs prevailing presently in India and their state wise performance in the year 2019-20, from the view of the insurance Industry is examined. How many persons are covered under GSHISs, amount of premium paid to the insurer under GSHISs, amount of claims paid by the insurer under GSHISs and number of claim paid by the insurer under GSHISs are the four factors considered for comparison. Abstract figures for all these factors and their comparisons against the other Group Health Insurance Policies and Total number of Health Policies are analyzed. It shows that the southern states like Tamil Nadu, Kerala, Goa are performing better than other states particularly the hilly states and Union Territories (UTs).